Religious Education Learning Practices Based on Local Wisdom in Islamic Schools - Najiyah, Siti Firqo; Prasetia, Senata Adi; Nabiilah, Zayyin (Jurnal Penelitian Pendidikan Islam, 2023)
This article describes the implementation of local wisdom-based learning in Antawirya Elementary School, Krian, Sidoarjo, East Java. The rise of schools that carry modern concepts i.e. integrated schools, international standard schools in their education has marginalized the local culture of Indonesia. Not only that, the majority of the younger generation has forgotten, not even knowing the local fairy tales and traditional games. In this context, Antawirya Krian Elementary School (SD) has a moral responsibility to develop the concept of learning based on local wisdom. This school rebranded itself as Islamic Javanese School. This is unique because local wisdom is the brand of the school and differentiates it from other schools. Through field research and data collection using documentation, observation and deep-interview, the findings of this article show the local wisdom carried by this school to practice traditional game-based learning and habituation to the local language, namely Javanese. In addition, learning based on local wisdom is able to increase the love of the homeland to learners. That's because the module “dolananku” presents a variety of traditional games that come from various regions in Indonesia. Thus, students know that their country, Indonesia has a variety of cultures that produce diversity.